Inheritance of major fatty acids in opium poppy (Papaver somniferum) - SINGH, S P; SHUKLA, SUDHIR; KHANNA, K R (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on different gene systems of opium poppy (Papaver somniferum L.) involved in the inher itmlce of major fatty acids, viz. palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1) and linoleic acid (C18:2) using 6 x 6 half diallel. ’BR 88’ for palmitic acid, ’BR 79’ for stearic acid and oleic acid and ’BR 76’ for linoleic acid were best combiners. The crosses ’BR 79’ X ’BR 76’ and ’BR 87’ x ’BR 85’ for oleic acid and ’IC 30’ X ’BR 85’ and ’BR 87’ X ’BR 76’ for linoleic acid had the highest value for the specific combining ability. The genetic combination of crosses were additive X dominance and dominance X dominance type due to involvement of high X low and low X low combiners. A negative association of oleic acid and linoleic acid was noticed and a breeding plan to develop genotypes with desired fatty acid composition was discussed.